The President's Legal Position in Doing The Reshuffle Of The Cabinet - La Ode Risman (LEGAL BRIEF, 2022)
The president has a very strong position in a government that adheres to a presidential system of government because in addition to being the head of government, the president is also the head of state. The President is based on Article 17 paragraph (2) of the 1945 Constitution of the Republic of Indonesia which states: The President appoints and dismisses ministers. The power that the President has over the powers granted by the Constitution of the Republic of Indonesia directly without interference from other institutions. This study aims to determine the legal position of the president in carrying out a cabinet reshuffle according to laws and regulations and to find out the legal consequences of a cabinet reshuffle carried out by the President. This research method uses normative legal research. The results of this study indicate that the power of the President in running the government is as the chief executive. In addition to the President and also the Vice President as the main center in the government, ministers are assisted. These ministers are not ordinary high-ranking employees but are technically executor of the president's duties. The president has a very strong position in a government that adheres to a presidential system of government because in addition to being the head of government.